2020
DOI: 10.1177/0963721420925546
|View full text |Cite
|
Sign up to set email alerts
|

The Situation of Situation Research: Knowns and Unknowns

Abstract: Over the past 15 years, research on the assessment of psychological situations has flourished. As a result, many basic questions about psychological situations have been answered. We discuss the theoretical and empirical studies that answered these questions, including what situations are; how they can be characterized, taxonomized, and measured; how they relate to person variables; and how persons navigate situations. We first summarize the “knowns” of psychological situation research and then proceed to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…Third, multiple approaches highlight the importance of environmental variables such as situations for the understanding of dynamics (e.g., Blum et al, 2018; Heller, Perunovic, & Reichman, 2009; Mischel & Shoda, 1995; Rauthmann, 2020a; Tett & Guterman, 2000; Wessels, Zimmermann, & Leising, 2016). For instance, Rauthmann (2020a) has systematized four types of person–environment relations (correlations, interactions, fits, transactions), and studying them has been facilitated by recent empirical and conceptual advances in the area of psychological situation research (e.g., Rauthmann, Horstmann, & Sherman, 2020; Rauthmann & Sherman, 2020).…”
Section: Contemporary Theoretical Dynamics‐focused Approaches In Persmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, multiple approaches highlight the importance of environmental variables such as situations for the understanding of dynamics (e.g., Blum et al, 2018; Heller, Perunovic, & Reichman, 2009; Mischel & Shoda, 1995; Rauthmann, 2020a; Tett & Guterman, 2000; Wessels, Zimmermann, & Leising, 2016). For instance, Rauthmann (2020a) has systematized four types of person–environment relations (correlations, interactions, fits, transactions), and studying them has been facilitated by recent empirical and conceptual advances in the area of psychological situation research (e.g., Rauthmann, Horstmann, & Sherman, 2020; Rauthmann & Sherman, 2020).…”
Section: Contemporary Theoretical Dynamics‐focused Approaches In Persmentioning
confidence: 99%
“…To gain a fuller picture of human functioning, it is important to assess not only variables pertaining to the person but also to the environment (Rauthmann, 2020a). The assessment of situational variables has made substantial progress over the last decade (Horstmann, Rauthmann, & Sherman, 2018; Rauthmann et al, 2020; Rauthmann & Sherman, 2020). Same as for the assessment of states, different types of information and data sources are relevant for the assessment of situations.…”
Section: Principles Of Empirical Research On Personality Dynamicsmentioning
confidence: 99%
“…Rauthmann and Sherman (2018) examined the empirical and theoretical convergences between the CAPTION and DIAMONDS dimensions and concluded that five replicable common dimensions could be retrieved (i.e., Negative Valence/Adversity, Adversity/Negativity, Importance/Duty, Complexity/Intellect, and Positive Valence/pOsitivity). More recently, Rauthmann and Sherman (2020) reviewed the overlap between the DIAMONDS and CAPTION dimensions and five other taxonomies of psychological situation characteristics that have been developed in the last decade. This suggested the existence of not five but six main situation dimensions: the five dimensions found in their previous work and an additional factor involving the mundaneness of the situation.…”
Section: Situation Characteristics and Taxonomiesmentioning
confidence: 99%
“…A recent surge in interest in the description of everyday situations resulted in various independent efforts that have led to (at least) two main comprehensive, psychologically relevant taxonomies of situation characteristics that subsume the gamut of important characteristics (for reviews and integrations, see Horstmann et al., 2018; Rauthmann, Horstmann, et al., 2020; Rauthmann & Sherman, 2018, 2020). The empirically based DIAMONDS dimensions describe situations based on their level of Duty, Intellect, Adversity, Mating, pOsitivity, Negativity, Deception, and Sociality (Rauthmann et al., 2014), while the lexically based CAPTION dimensions describe situations based on their level of Complexity, Adversity, Positive Valence, Typicality, Importance, humOr, and Negative Valence.…”
Section: Introductionmentioning
confidence: 99%
“…A reason for the relatively low contribution of the DIAMONDS dimensions to the annoyance perception may be that all participants rated individual sound situations and incorporated high diversity in objective environmental characteristics that were assessed-in the worst case-only once. The situational variables then become individual perceptions, i.e., personal variables (Rauthmann and Sherman, 2020). This represents a particular challenge for online studies and more valid field studies that must capture situations in a way that reduces otherwise enormous diversity.…”
Section: Discussionmentioning
confidence: 99%